l-Aspartate: An Essential Metabolite for Plant Growth and Stress Acclimation - Han, Mei; Zhang, Can; Suglo, Peter; Sun, Shuyue; Wang, Mingyao; Su, Tao (Molecules (Basel, Switzerland), 2021)
L-aspartate (Asp) serves as a central building block, in addition to being a constituent of proteins, for many metabolic processes in most organisms, such as biosynthesis of other amino acids, nucleotides, nicotinamide adenine dinucleotide (NAD), the tricarboxylic acid (TCA) cycle and glycolysis pathway intermediates, and hormones, which are vital for growth and defense. In animals and humans, lines of data have proved that Asp is indispensable for cell proliferation. However, in plants, despite the extensive study of the Asp family amino acid pathway, little attention has been paid to the function of Asp through the other numerous pathways. This review aims to elucidate the most important aspects of Asp in plants, from biosynthesis to catabolism and the role of Asp and its metabolic derivatives in response to changing environmental conditions. It considers the distribution of Asp in various cell compartments and the change of Asp level, and its significance in the whole plant under various stresses. Moreover, it provides evidence of the interconnection between Asp and phytohormones, which have prominent functions in plant growth, development, and defense. The updated information will help improve our understanding of the physiological role of Asp and Asp-borne metabolic fluxes, supporting the modular operation of these networks.